Customer Satisfaction in Online Banking : A Comparative Study of Local and Foreign Commercial Banks in the South of Vietnam, Ho Chi Minh City - Nguyen, Le Ngoc Diep (2014)
The purpose of this research is to construct a conceptual model with related instruments that affect customer satisfaction in using online banking in Ho Chi Minh City and Southern Vietnam. An important task of this work is the comparison of customer satisfaction in using online banking between customers of Vietnamese local banks and customers of foreign banks. Further discussions of the relationship among online service quality, perceived value, e-trust, relationship quality, customer satisfaction and customer loyalty are included. The results show that Vietnamese people are ethnocentric because there are 74% among 309 respondents currently using personal banking account of a Vietnam local bank. Exploratory analysis and regression analysis are made using SPSS for the observation of relationships between proposed factors. Respondents involved in the survey (quantitative method) are volunteers selected randomly while making sure that all of them are currently having personal banking accounts and have standard knowledge of using online banking. There are altogether 12 hypotheses in the proposed research model. The main findings of this work are: (1) Service quality positively influences perceived value; (2) Service quality positively influences e-trust; (3) Service quality positively influences customer satisfaction; (4) Perceived value positively influences e-trust; (5) E-trust positively influences customer satisfaction; (6) Perceived value positively influences loyalty; (7) Customer satisfaction positively loyalty; (8) Relationship positively influences e-trust; (9) Relationship quality positively influences customer satisfaction. Notice that the findings are especially for Vietnam online banking sector at Ho Chi Minh City.